Isolation, Screening for Bioactivities and Identification of Selected Endophyte Fungi by Sequencing of 18S RRNA/Its Genes - Cheah, Yoke Kqueen (2001)
Endophytic fungi occur within plant tissues such as leaves and stems of healthy plants without producing any apparent infections and symptoms. Experiments were conducted to isolate endophytic fungi from healthy medicinal plants as well as detecting any reoccurrence of any particular endophytic fungi predominantly in selected local medicinal plants. Endophytic fungi have also been recognised as repository of novel secondary metabolites, which have beneficial biological activities, biocontrol of insects and oligosaccharides degrading enzymes. Thus, isolated endophytic fungi were screened for their bioactive properties by using Thin Layer Chromatography and Agar Diffusion Assay. Specially engineered yeast strains i.e. UCS and UCK from Kyowa Hakko Company, Japan were used to screened for anti-tumour activity. 18S ribosomal Ribonucleic Acid (18S rRNA) I Internal Transcribed Spacer (ITS) gene sequencing were conducted to identified certain isolates. Isolation of the endophytic fungi from healthy local medicinal plants showed that 61 out of 72 (84.7%) yielded endophytic fungi. Most of the endophytes were obtained from the leaves and very few from the stems. The reoccurrence rate of the endophytic fungi was 1.39% (1 in 72). Nevertheless, no predominant endophytic fungi association with types of medicinal plant was observed. All the isolated endophytic fungi were able to degrade starch, xylan, mannan and inulin. 98.33% of the endophytic tested were able to degrade sago starch and rice starch. About 96.67% of the isolates were detected producing potato starch and starch wheat unmodified degrading enzyme. However, 95% of the endophytes produced tapioca starch and com starch degrading enzyme. Among the isolated endophytic fungi, 16.9% of them were considered important with regard to the bioactive screening results. Thus, 22 isolates from 130 isolated fungi gave satisfactory results in bioactive screening. There were 16 isolates that gave positive results in bio-activity test against UCS/UCK yeast strain. This showed that 16 out of 130 isolates produced potential bioactive compound for anti-tumour. Four out of the twenty two important isolates were identified through microscopic examination and 18S IITS gene sequencing. Isolate 12L was identified as Penicillium spp. through microscopic morphology observation. Those isolates identified by 18S IITS gene sequencing included 1B, Endothia gyrosa; 19L, Colfetotrichum gloeosporioides and 22L, Botryosphaeria ribis . BLAST programme was used as a tool to determine the homology of the sequence obtained with the database sequence.